“Eat the pain”. Food in the work of Marina Abramovic - Skenderija-Bohnet , Nikolina (E|C, 2020)
Marina Abramovic is Yugoslavian-born and New York based pioneer of performance art. By radically using her body as an artistic medium, she has been pushing it to the limit. While her early work included self-harming practices, Abramovic later moved on to long durational art form that is focused on meditative lingering where the emphasis lies on a spiritual or esoteric moment. In Abramovic’s entire oeuvre food plays an important role. She doesn’t use food as an object of art itself, but she creates her art around the symbolism and history of food, using it as a useful tool in her actual performance art. This general question of the role of food in Abramovic’s oeuvre will be the focus point of my article, while taking the closer look on certain performances such as: Thomas Lips (1975), Nightsea Crossing (1982), Balkan Baroque (1997), The Onion (1995), Spirit Cooking (1997), The Kitchen (2009).